Association of haemodynamic changes measured by serial central venous saturation during ultrafiltration for acutely decompensated heart failure with diuretic resistance and change in renal function. (1st October 2016) - Vazir, Ali; Simpkin, Victoria L.; Marino, Philip; Ludman, Andrew; Banya, Winston; Tavazzi, Guido; Bastin, Anthony J.; Trenfield, Sarah; Ghori, Arshad; Alexander, Peter D.; Griffiths, Mark; Price, Susanna; et al.
Abstract: Background: Patients with acute decompensated heart failure with diuretic resistance (ADHF-DR) have a poor prognosis. The aim of this study was to assess in patients with ADHF-DR, whether haemodynamic changes during ultrafiltration (UF) are associated with changes in renal function (Δcreatinine) and whether Δcreatinine post UF is associated with mortality. Methods: Seventeen patients with ADHF-DR underwent 20 treatments with UF. Serial bloods (4–6 hourly) from the onset of UF treatment were measured for renal function, electrolytes and central venous saturation (CVO2 ). Univariate and multivariate analysis were performed to assess the relationship between changes in markers of haemodynamics [heart rate (HR), systolic blood pressure (SBP), packed cell volume (PCV) and CVO2 ] and Δcreatinine. Patients were followed up and mortality recorded. Cox-regression survival analysis was performed to determine covariates associated with mortality. Results: Renal function worsened after UF in 17 of the 20 UF treatments (baseline vs. post UF creatinine: 164 ± 58 vs. 185 ± 69 μmol/l, P < 0.01). ΔCVO2 was significantly associated with Δcreatinine [β-coefficient of − 1.3 95%CI (− 1.8 to − 0.7), P < 0.001] and remained significantly associated with Δcreatinine after considering changes in SBP, HR and PCV [P < 0.001]. Ten (59%) patients died at 1-year and 15(88%) by 2-years. Δcreatinine was independently associated with mortality (adjusted-hazard ratio 1.03 (1.01 to 1.07) per 1 μmol/l increase in creatinine; P = 0.02). Conclusions: Haemodynamic changes during UF as measured by the surrogate of cardiac output was associated with Δcreatinine. Worsening renal function at end of UF treatment occurred in the majority of patients and was associated with mortality.